Pandemic (Im)mobilities - Adey, Peter; Hannam, Kevin; Sheller, Mimi; Tyfield, David (Mobilities, 2021)

Post-disaster Temporary Housing System based on Generative Design Method - Afonso, Filipe G.; Lu, Jun C. (International Journal of Structural and Civil Engineering Research, 2021)

The Probability Flow in the Stock Market and Spontaneous Symmetry Breaking in Quantum Finance - Arraut, Ivan; Lobo Marques, João Alexandre; Gomes, Sergio (Mathematics, 2021)
The spontaneous symmetry breaking phenomena applied to Quantum Finance considers that the martingale state in the stock market corresponds to a ground (vacuum) state if we express the financial equations in the Hamiltonian form. The original analysis for this phenomena completely ignores the kinetic terms in the neighborhood of the minimal of the potential terms. This is correct in most of the cases. However, when we deal with the martingale condition, it comes out that the kinetic terms can also behave as potential terms and then reproduce a shift on the effective location of the vacuum (martingale). In this paper, we analyze the effective symmetry breaking patterns and the connected vacuum degeneracy for these special circumstances. Within the same scenario, we analyze the connection between the flow of information and the multiplicity of martingale states, providing in this way powerful tools for analyzing the dynamic of the stock markets.
Keywords: Hermiticity; conservation of the information; degenerate vacuum; flow of information; martingale condition; random fluctuations; spontaneous symmetry breaking; vacuum condition

Personal Care and Cosmetic Products as a Potential Source of Environmental Contamination by Microplastics in a Densely Populated Asian City - Bashir, Saidu M.; Kimiko, Sam; Mak, Chu-Wa; Fang, James Kar-Hei; Gonçalves, David (Frontiers in Marine Science, 2021)
The prevalence of microplastics in the environment has become a major global conservation issue. One primary source of environmental microplastics is personal care and cosmetic products (PCCPs) containing microbeads. The market availability of PCCPs containing microbeads and the level of contamination of coastal sediments by microplastics was studied in one of the most densely populated cities in the world, Macao in China. We found that PCCPs containing microbeads are still widely available for sale in the region, with over 70% of surveyed PCCPs containing at least one type of microbeads as an ingredient, with polyethylene (PE) being the most common one. In an estimate, the use of PCCPs in the territory may release over 37 billion microbeads per year into the environment via wastewater treatment plants. The density of microplastics in coastal sediments varied between 259 and 1,743 items/L of sediment, amongst the highest reported in the world. The fraction of < 1 mm was the most abundant, representing an average of 98.6% of the total, and correlated positively with the abundance of larger sized fragments. The results show that although environmental pollution with microplastics released from PCCPs usage is significant, other sources, namely fragmentation of larger plastic debris, likely contribute more to the issue. The study highlights the magnitude of the problem at a local level and suggests possible mitigating strategies.

Chemical toxicity prediction based on semi-supervised learning and graph convolutional neural network - Chen, Jiarui; Si, Yain-Whar; Un, Chon-Wai; Siu, Shirley W. I. (Journal of Cheminformatics, 2021)
As safety is one of the most important properties of drugs, chemical toxicology prediction has received increasing attentions in the drug discovery research. Traditionally, researchers rely on in vitro and in vivo experiments to test the toxicity of chemical compounds. However, not only are these experiments time consuming and costly, but experiments that involve animal testing are increasingly subject to ethical concerns. While traditional machine learning (ML) methods have been used in the field with some success, the limited availability of annotated toxicity data is the major hurdle for further improving model performance. Inspired by the success of semi-supervised learning (SSL) algorithms, we propose a Graph Convolution Neural Network (GCN) to predict chemical toxicity and trained the network by the Mean Teacher (MT) SSL algorithm. Using the Tox21 data, our optimal SSL-GCN models for predicting the twelve toxicological endpoints achieve an average ROC-AUC score of 0.757 in the test set, which is a 6% improvement over GCN models trained by supervised learning and conventional ML methods. Our SSL-GCN models also exhibit superior performance when compared to models constructed using the built-in DeepChem ML methods. This study demonstrates that SSL can increase the prediction power of models by learning from unannotated data. The optimal unannotated to annotated data ratio ranges between 1:1 and 4:1. This study demonstrates the success of SSL in chemical toxicity prediction; the same technique is expected to be beneficial to other chemical property prediction tasks by utilizing existing large chemical databases. Our optimal model SSL-GCN is hosted on an online server accessible through: https://app.cbbio.online/ssl-gcn/home.
Keywords: ADMET; Chemical toxicity; Deep learning; Graph convolutional neural network; Mean teacher; Semi-supervised learning; Tox21

Home–School Collaboration in Assessment, Placement, and Individual Education Plan Development for Children With Special Education Needs in Macao: The Views of Parents - Correia, Ana; Teixeira, Vitor; Forlin, Chris (School Community Journal, 2021)
The aim of this study was to explore home–school collaboration in the areas of assessment, placement, and Individual Education Plan (IEP) development for children identified with disabilities or special educational needs (SEN) in Macao. Despite the noted benefits of parent–school partnerships from prior research, minimal research has been conducted from the perspective of parents of children with SEN to examine whether these partnerships materialize in the context of Macao. Participants included 115 parents of school-aged children diagnosed with SEN. They provided demographic information and completed a 36-item questionnaire derived from two validated instruments. The research identified a range of factors which hinder parental involvement in decision-making and in the inclusion of children with SEN in optimal ways in Macao schools. Parents indicated they were not receiving relevant information and assessment feedback from the teachers; they were minimally involved in the IEP process, and their children were not receiving one-to-one support, regardless of the type of placement. Parents also underlined issues related to the timing of assessment procedures. Parents of children attending special classes in regular schools voiced more satisfaction with support provision than parents of children following the full inclusion model. Recommendations about how services could be improved for greater parental involvement are discussed. Key Words: parental involvement, school–family collaboration, inclusion, special educational needs, Macao, Individual Education Plans, IEP

The Political and Economic Dependence of the Press in Macao under Portuguese and Chinese Rule: Continuity and Change - Costa-Ribeiro, Nelson; Simões, José Manuel (Communication & Society, 2021)
The article analyses the media system in Macao, a special administrative region of China that transitioned from Portuguese to Chinese sovereignty in 1999, becoming one of cities in the world with the largest number of published newspapers per capita. Combining historical research with the analysis of contemporary empirical data collected through interviews with journalists working on the ground, the research demonstrates how there is a long tradition of state control that goes back to the colonial era and that has assumed different forms, ranging from outright censorship to physical intimidation of journalists and economic dependence on the government. Limitations and control strategies imposed on news reporting during the Portuguese administration continue to be practiced today by the Chinese authorities. Even so, journalists operating on the Macao media market tend to overstate the level of freedom they are given, which can be attributed to media outlets being economically dependent on the state. Nevertheless, the level of freedom attributed to the press is today higher than it had been during the colonial period with some critical voices being allowed to reach the media. This needs to be understood in the context of what has been defined as the Chinese safety valve strategy.
Keywords: Censorship; Journalism Practice; Media Systems; Press Freedom; Press Subsidies

Divine foreknowledge and human free will: Embracing the paradox - DeVito, Michael; McNabb, Tyler Dalton (International Journal for Philosophy of Religion, 2021)

COVID-19: Psychological and Psychosocial Impact, Fear, and Passion - Dey, Nilanjan; Mishra, Rishabh; Fong, Simon James; Santosh, K. C.; Tan, Stanna; Crespo, Rubén González (Digital Government: Research and Practice, 2021)

Aristotle, Lubich And Ratzinger On A New Economic Paradigm - Eh, Edmond (The Journal of the Macau Ricci Institute, 2021)

Ethical Investment’s Visible Hand: Methods And Transformative Potentials - Gassner, Franz (The Journal of the Macau Ricci Institute, 2021)

“To Listen to the Language of Nature and to Act Accordingly” :: Natural Law as Beacon guiding to Human Flourishing and Ecological Civilization - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
The article sets off from a speech given by Benedict XVI in the German Bundestag in 2011, where he requested an ecological learning process to aim at sustainable human development. Appreciating the Ecological Movement, he asked to learn to listen to Nature’s language and act accordingly, which he applies analogically to “human ecology”. The article bridges elements of “Listening to Nature” and the Natural Moral Law Tradition in Benedict’s speech and in Francis’ Encyclical Letter Laudatu Si’ inview of serving human flourishing in an ecological civilization. Keywords: Natural Moral Law; Nature, Laudatu Si’, Benedict XVI, Francis; Ecological Civilization/生態文明, Sustainable Development, Ecology of Man.

Tourist’s mobilities: Walking, cycling, driving and waiting - Hannam, Kevin; Butler, Gareth; Witte, Alexandra; Zuev, Dennis (Tourist Studies, 2021)
This commentary reviews recent research in terms of tourist’s mobilities in terms practices of walking, cycling and driving. It concludes by reflecting on the contemporary lock down of travel in terms of the global pandemic and its consequences for waiting, stillness and immobility – particularly in terms of flying.

Data Augmentation for Deep Neural Networks Model in EEG Classification Task: A Review - He, Chao; Liu, Jialu; Zhu, Yuesheng; Du, Wencai (Frontiers in Human Neuroscience, 2021)
Classification of electroencephalogram (EEG) is a key approach to measure the rhythmic oscillations of neural activity, which is one of the core technologies of brain-computer interface systems (BCIs). However, extraction of the features from non-linear and non-stationary EEG signals is still a challenging task in current algorithms. With the development of artificial intelligence, various advanced algorithms have been proposed for signal classification in recent years. Among them, deep neural networks (DNNs) have become the most attractive type of method due to their end-to-end structure and powerful ability of automatic feature extraction. However, it is difficult to collect large-scale datasets in practical applications of BCIs, which may lead to overfitting or weak generalizability of the classifier. To address these issues, a promising technique has been proposed to improve the performance of the decoding model based on data augmentation (DA). In this article, we investigate recent studies and development of various DA strategies for EEG classification based on DNNs. The review consists of three parts: what kind of paradigms of EEG-based on BCIs are used, what types of DA methods are adopted to improve the DNN models, and what kind of accuracy can be obtained. Our survey summarizes the current practices and performance outcomes that aim to promote or guide the deployment of DA to EEG classification in future research and development.

A Preliminary Psychometric Investigation of a Chinese Version of the Engaged Teachers Scale (C-ETS) - Ho, Sammy K.; Chan, Hang; Chan, Edmund Sze-Shing; Fung, Kwok-Kin; Hung, Shirley Suet-Lin (Frontiers in Education, 2021)
This study examines the psychometric properties of a Chinese version of the Engaged Teacher Scale (C-ETS). A translated questionnaire with 16 items was administered to a sample of 341 primary and secondary school teachers in Hong Kong. A series of confirmatory factor analyses were performed to assess the construct, convergent, and discriminant validity of the scale in alternative models. Results provide support for a second-order model with teacher engagement as an overarching construct with four hypothesized dimensions: emotional engagement, cognitive engagement, social engagement (students), and social engagement (colleagues). The C-ETS provides a useful measure for teacher engagement in Chinese societies. Contributions and limitations of the study are discussed.

Can mangroves work as an effective phytoremediation tool for pesticide contamination? An interlinked analysis between surface water, sediments and biota - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Cruzeiro, Catarina; Tagulao, Karen Arano (Journal of Cleaner Production, 2021)
Mangroves are a unique group of plants growing along tropical and sub-tropical coastlines, with the ability to remove several types of contaminants such as heavy metals and other persistent organic compounds in coastal waters. However, little attention has been given to the possible role of mangroves in the removal of organochlorinated pesticides (OCPs) from the environment. Used worldwide, these pesticides were banned in the late 80s, withal they can still be quantified in aquatic environments due to their high stability. Moreover, as persistent and lipophilic compounds, OCPs are known for their tendency to bioaccumulate and biomagnify through the food chain, affecting local ecosystems, and potentially human health. This work aimed to investigate the potential benefits of mangrove ecosystems as OCP phytoremediators. For this purpose, a total of seventy-three articles from non-mangrove and mangrove areas around the world were gathered, integrated and re-analysed as a whole. These data include information from four different matrices (water, sediment, benthic fauna and mangrove plants). A common trend of less pesticide contamination in mangrove areas was observed for all the selected matrices. As a complement, average concentrations were discussed considering International Directives, such as the European legislation 2013/39/EU for water policy and the Dutch List together with the International Sediment Quality Guideline, for sediments. Additionally, theoretical risk assessments were also included. Since information regarding OCPs in mangroves ecosystem is very scarce compared to non-mangrove areas, this review provides valuable insights regarding these environments, and the importance of preserving them as a relevant remediation unit.
Keywords: Benthic fauna; Intertidal environments; Organochlorinated pesticides; Persistent organic compounds; Toxicological assessment

International collaboration for mutual benefit: a Southwest China and Southeast United States partnership - Jackson, M. Sebrena; Gardell, Debra Nelson; Williams, Javonda; Tang, Ning; Yang, Fan (China Journal of Social Work, 2021)
China’s return to social work education, after a nearly 35-year absence, opened the door for partnerships like the 2012 China Collaborative partnership between the Council on Social Work Education’s (CSWE) Katherine A. Kendall Institute, the China Association of Social Work Education (CASWE) and the International Association of Schools of Social Work (IASSW). The University of Alabama School of Social Work (UA SSW) was selected to participate in the collaborative and was connected to the Southwest China Region, specifically partnered with Yunnan University. This manuscript will share the strategies used to engage faculty and students from each partnering institution. Data collected by UA SSW over the five-year partnership will be utilised to contribute to the discussion of the extent to which Western knowledge and theory about social work education might usefully be applied to the Chinese context.
Keywords: China collaborative; International social work; University of Alabama; Yunnan University; social work education

Elite athletes’ mental well-being and life satisfaction: a study of elite athletes’ resilience and social support from an Asian unrecognisedNational Olympic Committee - Kuok, A. C. H; K. I. Chio, David; C. H. Pun, Alan (Health Psychology Report, 2021)
Introduction This study aimed to investigate elite athletes’ mental well-being, and to ascertain whether the personal factor resilience and the social factor social support can play a role in promoting mental well-being and life satisfaction. In addition, this is one of the first studies to investigate well-being among elite athletes who are from a region belonging to an unrecognised National Olympic Committee and are not eligible to join the Olympic Games. Material and methods Eighty-four full-time elite athletes (37 males, 47 females) with mean age of 22.36 years old participated in this quantitative research study. Formal letters describing the purpose and organiser of the study were sent to the sport entities in Macao asking their permission for the researchers to contact the elite athletes to participate in this study. After gaining the permission, the elite athletes belonging to these entities were approached individually, to inform them of the purpose of the study and receive their consent. Results Regression revealed that emotional support and adaptability of resilience were strong positive predictors of mental well-being. Additionally, mental well-being was found to be a strong positive predictor of life satisfaction. The results reflected that in elite athletes possessing high adaptability and receiving more emotional support could help to maintain their mental well-being. Conclusions Implications (based on the findings) are discussed in order to provide insights for policy makers or coaches how to promote elite athletes’ mental well-being.

Impact of noise on development, physiological stress and behavioural patterns in larval zebrafish - Lara, Rafael A.; Vasconcelos, Raquel O. (Scientific Reports, 2021)
Noise pollution is increasingly present in aquatic ecosystems, causing detrimental effects on growth, physiology and behaviour of organisms. However, limited information exists on how this stressor affects animals in early ontogeny, a critical period for development and establishment of phenotypic traits. We tested the effects of chronic noise exposure to increasing levels (130 and 150 dB re 1 μPa, continuous white noise) and different temporal regimes on larval zebrafish (Danio rerio), an important vertebrate model in ecotoxicology. The acoustic treatments did not affect general development or hatching but higher noise levels led to increased mortality. The cardiac rate, yolk sac consumption and cortisol levels increased significantly with increasing noise level at both 3 and 5 dpf (days post fertilization). Variation in noise temporal patterns (different random noise periods to simulate shipping activity) suggested that the time regime is more important than the total duration of noise exposure to down-regulate physiological stress. Moreover, 5 dpf larvae exposed to 150 dB continuous noise displayed increased dark avoidance in anxiety-related dark/light preference test and impaired spontaneous alternation behaviour. We provide first evidence of noise-induced physiological stress and behavioural disturbance in larval zebrafish, showing that both noise amplitude and timing negatively impact key developmental endpoints in early ontogeny.
Keywords: Embryology; Environmental impact; Freshwater ecology

Does Romans 2:14 Refer to the Natural Law? - Leong, Chi Hei (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
Whilst after decades of research, exegetes have all agree on the complexity of Paul’s line of thinking in Rom 2:14–16, the ITC in its 2009 document, In Search of a Universal Ethic, still in an oversimplified manner propagates the view that Rom 2:14 presupposes a theory/theology of the natural law. This article makes plain the major disagreements among Pauline exegetes whether such presupposition stands by reviewing some major contributions to the discussion by raising major questions regarding the issue of φύσει in those verses, the nature of the law mentioned by Paul, the identity of the people Paul calls “Gentiles.” This article offers a more nuanced understanding of Rom 2:14. Keywords: Rom 2:14, ITC, Universal Ethic, Natural Law, φύσει, Gentiles

An Improved Double Channel Long Short-Term Memory Model for Medical Text Classification - Liang, Shengbin; Chen, Xinan; Ma, Jixin; Du, Wencai; Ma, Huawei (Journal of Healthcare Engineering, 2021)
There are a large number of symptom consultation texts in medical and healthcare Internet communities, and Chinese health segmentation is more complex, which leads to the low accuracy of the existing algorithms for medical text classification. The deep learning model has advantages in extracting abstract features of text effectively. However, for a large number of samples of complex text data, especially for words with ambiguous meanings in the field of Chinese medical diagnosis, the word-level neural network model is insufficient. Therefore, in order to solve the triage and precise treatment of patients, we present an improved Double Channel (DC) mechanism as a significant enhancement to Long Short-Term Memory (LSTM). In this DC mechanism, two channels are used to receive word-level and char-level embedding, respectively, at the same time. Hybrid attention is proposed to combine the current time output with the current time unit state and then using attention to calculate the weight. By calculating the probability distribution of each timestep input data weight, the weight score is obtained, and then weighted summation is performed. At last, the data input by each timestep is subjected to trade-off learning to improve the generalization ability of the model learning. Moreover, we conduct an extensive performance evaluation on two different datasets: cMedQA and Sentiment140. The experimental results show that the DC-LSTM model proposed in this paper has significantly superior accuracy and ROC compared with the basic CNN-LSTM model.

An improved ant colony optimization algorithm based on context for tourism route planning - Liang, Shengbin; Jiao, Tongtong; Du, Wencai; Qu, Shenming (PLOS ONE, 2021)
To solve the problem of one-sided pursuit of the shortest distance but ignoring the tourist experience in the process of tourism route planning, an improved ant colony optimization algorithm is proposed for tourism route planning. Contextual information of scenic spots significantly effect people’s choice of tourism destination, so the pheromone update strategy is combined with the contextual information such as weather and comfort degree of the scenic spot in the process of searching the global optimal route, so that the pheromone update tends to the path suitable for tourists. At the same time, in order to avoid falling into local optimization, the sub-path support degree is introduced. The experimental results show that the optimized tourism route has greatly improved the tourist experience, the route distance is shortened by 20.5% and the convergence speed is increased by 21.2% compared with the basic algorithm, which proves that the improved algorithm is notably effective.

Acculturative stress and coping among migrant workers: A global mixed-methods systematic review - Liem, Andrian; Renzaho, Andre M. N.; Hannam, Kevin; Lam, Agnes I. F.; Hall, Brian J. (Applied Psychology: Health and Well-Being, 2021)
No existing review has synthesized key questions about acculturation experiences among international migrant workers. This review aimed to explore (1) What are global migrant workers’ experiences with acculturation and acculturative stress? (2) What are acculturative stress coping strategies used by migrant workers? And (3) how effective are these strategies for migrant workers in assisting their acculturation in the host countries? Peer-reviewed and gray literature, without time limitation, were searched in six databases and included if the study: focused on acculturative stress and coping strategies; was conducted with international migrant workers; was published in English; and was empirical. Eleven studies met the inclusion criteria. Three-layered themes of acculturation process and acculturative stress were identified as: individual layer; work-related layer; and social layer. Three key coping strategies were identified: emotion-focused; problem-focused; and appraisal-focused. These coping strategies were used flexibly to increase coping effectiveness and evidence emerged that a particular type of acculturative stress might be solved more effectively by a specific coping strategy. Migrant workers faced numerous challenges in their acculturative process. Understanding this process and their coping strategies could be used in developing research and interventions to improve the well-being of migrant workers.
Keywords: acculturation; cultural adaptation; global mental health; health disparities; healthcare access; migrant health

IoT-Based Smart Health System for Ambulatory Maternal and Fetal Monitoring - Marques, João Alexandre Lobo; Han, Tao; Wu, Wanqing; Madeiro, João Paulo do Vale; Neto, Aloísio Vieira Lira; Gravina, Raffaele; Fortino, Giancarlo; de Albuquerque, Victor Hugo C. (IEEE Internet of Things Journal, 2021)
The adoption of IoT for smart health applications is a relevant tool for distributed and intelligent automatic diagnostic systems. This work proposes the development of an integrated solution to monitor maternal and fetal signals for high-risk pregnancies based on IoT sensors, feature extraction based on data analytics, and an intelligent diagnostic aid system based on a 1-D convolutional neural network (CNN) classifier. The fetal heart rate and a group of maternal clinical indicators, such as the uterine tonus activity, blood pressure, heart rate, temperature, and oxygen saturation are monitored. Multiple data sources generate a significant amount of data in different formats and rates. An emergency diagnostic subsystem is proposed based on a fog computing layer and the best accuracy was 92.59% for both maternal and fetal emergency. A smart health analytics system is proposed for multiple feature extraction and the calculation of linear and nonlinear measures. Finally, a classification technique is proposed as a prediction system for maternal, fetal, and simultaneous health status classification, considering six possible outputs. Different classifiers are evaluated and a proposed CNN presented the best results, with the F1-score ranging from 0.74 to 0.91. The results are validated based on the diagnosis provided by two specialists. The results show that the proposed system is a viable solution for maternal and fetal ambulatory monitoring based on IoT.
Keywords: Artificial intelligence (AI); Biomedical monitoring; Cloud computing; Feature extraction; Fetal heart rate; Internet of Things; Medical diagnostic imaging; Monitoring; convolutional neural networks (CNNs); feature extraction; fetal monitoring; health analytics; maternal monitoring

Houston, Do We Have a Problem?: Extraterrestrial Intelligent Life and Christian Belief - McIntosh, C. A.; McNabb, Tyler Dalton (Philosophia Christi, 2021)
Would the existence of extraterrestrial intelligent life (ETI) conflict in any way with Christian belief? We identify six areas of potential conflict. If there be no conflict in any of these areas—and we argue ultimately there is not—we are confident in declaring that there is no conflict, period. This conclusion underwrites the integrity of theological explorations into the existence of ETI, which has become a topic of increasing interest among theologians in recent years.

Papal Bull: A Response to Contemporary Papal Scholarship - McNabb, Tyler Dalton (Journal of Biblical and Theological Studies, 2021)

Basic Beliefs, the Embryo Rescue Case, and Single-Issue Voting: A Response to Dustin Crummett - McNabb, Tyler; DeVito, Michael (The National Catholic Bioethics Quarterly, 2021)
In this essay, we respond to Dustin Crummett’s argument that one cannot consistently appeal to body count reasoning to justify being a single-issue pro-life voter if one is also committed to the usual response to the embryo rescue case. Specifically, we argue that a modified version of BCR we call BCR* is consistent with the usual response. We then move to address concerns about the relevance of BCR* to Crummett’s original thesis.

Sediments in the mangrove areas contribute to the removal of endocrine disrupting chemicals in coastal sediments of Macau SAR, China, and harbour microbial communities capable of degrading E2, EE2, BPA and BPS - Moreira, Irina S.; Lebel, Alexandre; Peng, Xianzhi; Castro, Paula M. L.; Gonçalves, David (Biodegradation, 2021)
The occurrence of endocrine disrupting chemicals (EDCs) is a major issue for marine and coastal environments in the proximity of urban areas. The occurrence of EDCs in the Pearl River Delta region is well documented but specific data related to Macao is unavailable. The levels of bisphenol-A (BPA), estrone (E1), 17α-estradiol (αE2), 17β-estradiol (E2), estriol (E3), and 17α-ethynylestradiol (EE2) were measured in sediment samples collected along the coastline of Macao. BPA was found in all 45 collected samples with lower BPA concentrations associated to the presence of mangrove trees. Biodegradation assays were performed to evaluate the capacity of the microbial communities of the surveyed ecosystems to degrade BPA and its analogue BPS. Using sediments collected at a WWTP discharge point as inoculum, at a concentration of 2 mg l−1 complete removal of BPA was observed within 6 days, whereas for the same concentration BPS removal was of 95% after 10 days, which is particularly interesting since this compound is considered recalcitrant to biodegradation and likely to accumulate in the environment. Supplementation with BPA improved the degradation of bisphenol-S (BPS). Aiming at the isolation of EDCs-degrading bacteria, enrichments were established with sediments supplied with BPA, BPS, E2 and EE2, which led to the isolation of a bacterial strain, identified as Rhodoccoccus sp. ED55, able to degrade the four compounds at different extents. The isolated strain represents a valuable candidate for bioremediation of contaminated soils and waters.
Keywords: Biodegradation; Bisphenols; EDCs-degrading bacteria; Endocrine disrupting chemicals (EDCs); Estrogens; Mangrove

Ceremonies of the Sarum Missal: A Careful Conjecture by R. J. Urquhart (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2021)

‘Em Procissão Solene a Deus Orando, para os Batéis Viemos Caminhando’—The Long Ebb-Tide of Catholic Public Piety in the Former-Portuguese Enclave of Macao - Morgan, Stephen (Religions, 2021)
When the City of the Name of God of Macao marked 400 years of Portuguese administration in 1956, the Catholic community’s participation was marked by a wide range of activities that included liturgical celebrations, public processions and other devotions that involved large numbers of the lay faithful, members of confraternities, in addition to the clergy and religious of the enclave. Twenty-one years later the Diocese of Macao celebrated its own quatercentenary with celebrations of a decidedly more sober character and at the retrocession of Macao to Chinese control in December 1999, other than a few liturgical events and hierarchical presence at civic ceremonies, the Church was all but invisible. As the Diocese of Macao plans for its 450th anniversary, some of the former richness has begun to return. This paper outlines the long ebb tide and now-nascent flow of the tide of Catholic public piety in Macao over this period by reference to the Catholic religious processions of the City and seeks to offer tentative explanations grounded in the theological, ecclesial, political and cultural winds that have blown across the Pearl River Delta since the end of the Second World War.
Keywords: Catholic Church; China; Macao; Portugal; Vatican II; confrarias; processions; public piety

‘Navigation for an ocean of interminable scepticism’ revisited: John Henry Newman and the place of theology in the university - Morgan, Stephen (International Journal for the Study of the Christian Church, 2021)
The place of theology is under threat in the modern university. It is denied a place, except insofar as it is useful in the training of religious professionals or as a phenomenon in its own right, on the grounds that relate to an unscientific scientism that both makes metaphysical assumptions it itself does not recognise as scientific or denies its own epistemological commitments. This article argues that the notion of education in ‘liberal knowledge’ or ‘universal knowledge’, the idea at the heart of John Henry Newman’s The Idea of a University provides a sufficiently robust counter to these assaults on the place of theology proper in the modern university and that refusing such a place to it undermines the claim of universities to use the name at all. It is precisely the uselessness of theology that guarantees its place in the university committed to universal knowledge and universal enquiry.
Keywords: Derrida; Newman; education; liberal education; religious studies; secularisation; theology; university

The Anglican Patrimony in Catholic Communion ed. by Tracey Rowland (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2021)

Identification of Latent Risk Clinical Attributes for Children Born Under IUGR Condition Using Machine Learning Techniques - Nguyen Van, Sau; Lobo Marques, J. A.; Biala, T. A.; Li, Ye (Computer Methods and Programs in Biomedicine, 2021)
Background and objective Intrauterine Growth Restriction (IUGR) is a condition in which a fetus does not grow to the expected weight during pregnancy. There are several well documented causes in the literature for this issue, such as maternal disorder, and genetic influences. Nevertheless, besides the risk during pregnancy and labour periods, in a long term perspective, the impact of IUGR condition during the child development is an area of research itself. The main objective of this work is to propose a machine learning solution to identify the most significant features of importance based on physiological, clinical or socioeconomic factors correlated with previous IUGR condition after 10 years of birth. Methods In this work, 41 IUGR (18 male) and 34 Non-IUGR (22 male) children were followed up 9 years after the birth, in average (9.1786 ± 0.6784 years old). A group of machine learning algorithms is proposed to classify children previously identified as born under IUGR condition based on 24-hours monitoring of ECG (Holter) and blood pressure (ABPM), and other clinical and socioeconomic attributes. In additional, an algorithm of relevance determination based on the classifier is also proposed, to determine the level of importance of the considered features. Results The proposed classification solution achieved accuracy up to 94.73%, and better performance than seven state-of-the-art machine learning algorithms. Also, relevant latent factors related to HRV and BP monitoring are proposed, such as: day-time heart rate (day-time HR), day-night systolic blood pressure (day-night SBP), 24-hour standard deviation (SD) of SBP, dropped, morning cortisol creatinine, 24-hour mean of SDs of all NN intervals for each 5 minutes segment (24-hour SDNNi), among others. Conclusion With outstanding accuracy of our proposed solutions, the classification system and the indication of relevant attributes may support medical teams on the clinical monitoring of IUGR children during their childhood development.
Keywords: ABPM (Ambulatory Blood Pressure Monitoring); HRV (Heart Rate Variability); IUGR (Intrauterine Growth Restriction); Machine Learning

Relações entre o pós-digital e o complexo industrial do capitalismo: reformulações sobre a tecnologia como ideologia e lixo digital na arte - Paquete, Hugo; Fernandes-Marcos, Adérito; Bastos, Paulo Bernardino (AVANCA | CINEMA, 2021)
This essay presents a mapping of the historical concepts that contributed to the emergence of post-digital aesthetics and their connections to the concept of post-media in historical terms. It also analyzes the transition from techno-positivism to discourse of resistance against the effects of the capital technological industrial complex and how these advances in technology influence artistic discourses, practices and are the leverage of art and technology which is nothing more than a representation of the aesthetics of capital. Following art and capitalism as an ideology of innovation. Is proposed an unstinting theory about technology, geology, and the importance of these conditions to the post-digital aesthetics in terms of material disponible and conceptual articulation. Producing a reconfiguration of the post-digital conceptual approach as I propose beyond the dysfunctional aesthetics and connected with the concept of radical ecology centered in the usability of electronic garbage and technical obsolescent technologies in the arts.

Post-Digital Fashion: The Evolution and Creation Cycle - Pereira, Selma; Fernandes-Marcos, Adérito (ZoneModa Journal, 2021)
In the face of the Covid-19 pandemic, the fashion industry was surprised and quickly had to adapt to digital media. However, the relationship between fashion and the multiplicity of screens is not new. Fashion emerged and took its first steps with Cinema, in Modernity. Although there are times when these two systems are further apart from each other, the alliance survived. To analyse contemporaneity, we take as main reference the studies of Gilles Lipovetsky, and his reflections on aesthetic capitalism. The fashion system has many Western fields of life, including art and technology. In this article we discuss how this relationship of fashion adapts and develops with aesthetic capitalism and post-digital art while we analyse representative artefacts from/about fashion. We propose to put the recent digital fashion artefacts in dialogue with post-digital aesthetics theories, discussing the blurred boundaries between the digital and the post-digital, and proposing the instantiation of a post-digital creation cycle applied to fashion artefacts.

A performance académica como ritual de criação e ativismo na era pós-digital - Pérez, P; Pereira, S; Fernandes-Marcos, A (AVANCA CINEMA, 2021)

Malacca Portuguese Creole - Pillai, Stefanie; Baxter, Alan N.; Soh, Wen-Yi (Journal of the International Phonetic Association, 2021)
Malacca Portuguese Creole (MPC) (ISO 639-3; code: mcm), popularly known as Malacca Portuguese or locally as (Papiá) Cristang, belongs to the group of Portuguese-lexified creoles of (South)east Asia, which includes the extinct varieties of Batavia/Tugu (Maurer 2013) and Bidau, East Timor (Baxter 1990), and the moribund variety of Macau (Baxter 2009). MPC has its origins in the Portuguese presence in Malacca, and like the other creoles in this subset, it is genetically related to the Portuguese Creoles of South Asia (Holm 1988, Cardoso, Baxter & Nunes 2012).

Constraints of Fe-S-C stable isotopes on hydrothermal and microbial activities during formation of sediment-hosted stratiform sulfide deposits - Qiu, Wenhong Johnson; Zhou, Mei-Fu; Li, Xiaochun; Huang, Fang; Malpas, John (Geochimica et Cosmochimica Acta, 2021)
Microbial and hydrothermal venting activities on the seafloor are important for the formation of sediment-hosted stratiform sulfide (SHSS) deposits. Fe isotopic compositions are sensitive to both microbial and hydrothermal activities and may be used to investigate the formation of these deposits. However, to the best of our knowledge, no Fe isotopic studies have been conducted on SHSS deposits. In the Devonian Dajiangping SHSS-type pyrite deposit (389 Ma), South China, laminated pyrite ores were precipitated from exhalative hydrothermal fluids, whereas black shales were deposited during intervals with no exhalation. Pyrite grains from black shales mostly display positive δ56Fe-py (0.01–0.73‰), higher than marine sediments (ca. 0‰), due to pyrite deriving Fe from basinal shuttled Fe(III) (hydr-)oxides and slowly crystallizing in pores of sediments with equilibrium fractionation, except for negative δ56Fe-py (−0.17‰ to −0.24‰) of two samples caused by mixing of Fe from underlain laminated ores. The positive δ34S-py (3.50–24.5‰) of black shales reflect that sulfur of pyrite originated from quantitative reduction of sulfate in closed pores of sediments. In contrast, pyrite grains of laminated ores have negative δ56Fe-py (−0.60‰ to −0.21‰), which were not only inherited from the negative δ56Fe of hydrothermal fluids but also caused by kinetic fractionation during rapid precipitation of a pyrite precursor (FeS) in hydrothermal plumes. These ores have negative δ34S-py (−28.7‰ to −1.82‰), because H2S for pyrite mineralization was produced by bacterial sulfate reduction (BSR) in a sulfate-rich seawater column or shallow sediments. The δ56Fe-py values of laminated ores co-vary positively with δ34S-py and δ13C-carbonate along the ore stratigraphy, with δ13C-carbonate values ranging from −12.0‰ to −2.50‰. However, they correlate negatively with aluminum-normalized total organic carbon (TOC/Al2O3). Organic carbon is thus considered to enhance the production of H2S by BSR activities, increase pyrite precipitation rates and promote the expression of kinetic fractionation of Fe isotopes. Intriguingly, in the ore units with vigorous hydrothermal venting activities, δ56Fe-py, δ34S-py and δ13C-carbonate values display a consistently increasing trend. Such results suggest that venting hydrothermal fluids significantly inhibited the H2S production of BSR, which then reduced the pyrite crystallization rate and decreased the kinetic fractionation of Fe isotopes. Our study reveals that the formation of SHSS deposits relies on H2S from microbial activities and metals from hydrothermal exhalation on the seafloor, but that vigorous exhalation can inhibit microbial activities and thus sulfide precipitation rates. The integrated use of Fe, S, and C isotopes can effectively elucidate these dynamic interactions between hydrothermal venting and microbial activities during the formation of SHSS deposits.
Keywords: Iron isotope; Isotope fractionation; Sediment-hosted stratiform sulfide deposit; Sulfur isotope

Geological Map of the Macao Special Administrative Region (China) - Quelhas, P; Borgens, R; Dias, Ágata; Ribeiro, L; Costa, P; Mata, J (Journal of Maps, 2021)

Geology of the Macao Special Administrative Region (China) - Quelhas, Pedro; Borges, Ricardo; Dias, Ágata Alveirinho; Ribeiro, Maria Luísa; Costa, Pedro; Mata, João (Journal of Maps, 2021)
A 1:12,000 geological map of the Macao Special Administrative Region has been produced through detailed field work supported by petrographic, mineralogical, geochronological and geochemical data obtained in previous studies. This map aims to represent a reliable tool to understand the geological evolution of the region and for management of the territory. The geology of Macao is dominated by two groups of Jurassic granitic rocks belonging to an intrusive suite located along the coast of Southeast China: Macao Group I (MGI: 164.5 ± 0.6 to 162.9 ± 0.7 Ma) and Macao Group II (MGII: 156.6 ± 0.2 to 155.5 ± 0.8 Ma), including the associated microgranite, aplite and pegmatite dikes and quartz veins. Remnants of the metasedimentary wall-rock are present as Devonian xenoliths enclosed within the granites. Younger Jurassic to Cretaceous andesite to dacite dikes (150.6 ± 0.6 to <120 Ma) intrude the granitic rocks. Additionally, Quaternary sedimentary deposits cover the older lithologies.
Keywords: Jurassic; Macao (South China); Mesozoic; geological map; granites; magmatic rocks

Evidence for mixed contribution of mantle and lower and upper crust to the genesis of Jurassic I-type granites from Macao, SE China - Quelhas, Pedro; Mata, João; Dias, Ágata (GSA Bulletin, 2021)
Abstract Much controversy has occurred in the past few decades regarding the nature of the sources, the petrogenetic processes, and the tectonic regime(s) of the Jurassic magmatism within the Southeast China magmatic belt. This study aims to contribute to the discussion with mineral chemistry, and whole-rock element and Sr-Nd-Hf-Pb isotopic geochemical data from granitic rocks and microgranular mafic enclaves from Macao, where two discrete groups of I-type biotite granites have been identified (referred to as Macao Group I [MGI] and Macao Group II [MGII]). It is proposed that the granitic magmas were generated by partial melting of infracrustal medium- to high-K, basaltic Paleoproterozoic to Mesoproterozoic protoliths (Nd depleted mantle model age [TDM2] = 1.7–1.6 Ga and Hf TDM2 = 1.8–1.6 Ga), triggered by underplating of hot mantle-derived magmas in an extensional setting related to the foundering of a previously flat slab (paleo–Pacific plate) beneath the SE China continent. The main differences between the two groups of Macao granites are attributed to assimilation and fractional crystallization processes, during which upper-crustal Paleozoic metasediments were variably assimilated by MGI magmas. This is evidenced by an increase in initial 87Sr/86Sr ratios with degree of evolution, presence of metasedimentary enclaves, and high percentage of zircon xenocrysts with Paleozoic ages. In addition, other processes like late-stage fluid/melt interaction and magma mixing also left some imprints on granite compositions (rare earth element tetrad effect plus non–charge-and-radius-controlled behavior of trace elements and decoupling between different isotope systems, respectively). The distribution of isotopically distinct granites in SE China reflects the nature of the two Cathaysia crustal blocks juxtaposed along the Zhenghe-Dapu fault.

Magmatic Evolution of Garnet-Bearing Highly Fractionated Granitic Rocks from Macao, Southeast China: Implications for Granite-Related Mineralization Processes - Quelhas, Pedro; Mata, João; Dias, Ágata (Journal of Earth Science, 2021)
The widespread W-(Mo)-Sn-Nb-Ta polymetallic mineralization in Southeast (SE) China is genetically associated with Mesozoic highly fractionated granitic rocks. Such rocks have enigmatic mineralogical and geochemical features, making its petrogenesis an intensely debated topic. To better understand the underlying magma evolution processes, petrography, garnet chemistry and whole-rock major and trace element data are reported for Jurassic highly fractionated granitic rocks and associated microgranite and aplitepegmatite dikes from Macao and compared with coeval similar granitic rocks from nearby areas in SE China. Despite the fact that the most evolved rocks in Macao are garnet-bearing aplite-pegmatite dikes, the existence of coeval two-mica and garnet-bearing biotite and muscovite granites displaying more evolved compositions (e.g, lower Zr/Hf ratios) indicates that the differentiation sequence reached higher degrees of fractionation at a regional scale. Although crystal fractionation played an important role, late-stage fluid/melt interactions, involving F-rich fluids, imparted specific geochemical characteristics to Macao and SE China highly fractionated granitic rocks such as the non-CHARAC (CHArge-and-RAdius-Controlled) behavior of trace elements, leading, for example, to non-chondritic Zr/Hf ratios, Rare Earth Elements (REE) tetrad effects and Nb-Ta enrichment and fractionation. Such process contributed to the late-stage crystallization of accessory phases only found in these highly evolved facies. Among the latter, two populations of garnet were identified in MGI (Macao Group I) highly fractionated granitic rocks: small grossular-poor euhedral grains and large grossular-rich skeletal garnet grains with quartz inclusions. The first group was mainly formed through precipitation from highly evolved Mn-rich slightly peraluminous melts under low-pressure and relatively low temperature (∼700 °C) conditions. Assimilation of upper crust metasedimentary materials may have contributed as a source of Mn and Al to the formation of garnet. The second group has a metasomatic origin related to the interaction of magmatic fluids with previously crystallized mineral phases and, possibly, with assimilated metasedimentary enclaves or surrounding metasedimentary strata. The highly fractionated granitic rocks in Macao represent the first stage in the development of granite-related W-(Mo)-Sn-Nb-Ta mineralization associated with coeval more evolved lithotypes in SE China.

Androgens and corticosteroids increase in response to mirror images and interacting conspecifics in males of the Siamese fighting fish Betta splendens - Ramos, Andreia; Alex, Deepa; Cardoso, Sara D.; Gonçalves, David (Hormones and Behavior, 2021)
The role of hormones as modulators of aggressive behavior in fish remains poorly understood. Androgens and corticosteroids, in particular, have been associated with aggressive behavior in fish but it is still not clear if animals adjust the secretion of these hormones to regulate behavior during ongoing fights, in response to fight outcomes in order to adjust aggressive behavior in subsequent fights, or both. With its stereotyped displays and high aggression levels, the Siamese fighting fish Betta splendens is an excellent model to investigate this question. Here, we compared the behavioral and endocrine response of male B. splendens to fights where there is no winner or loser by presenting them with a size-matched live interacting conspecific behind a transparent partition or with a mirror image. The aggressive response started with threat displays that were overall similar in frequency and duration towards both types of stimuli. Fights transitioned to overt attacks and interacting with a live conspecific elicited a higher frequency of attempted bites and head hits, as compared with the mirror image. There was a pronounced increase in plasma androgens (11-ketotestosterone and testosterone) and corticosteroids (cortisol) levels in response to the aggression challenge, independent of stimulus type. Post-fight intra-group levels of these hormones did not correlate with measures of physical activity or aggressive behavior. A linear discriminant analysis including all behavioral and endocrine data was a poor classifier of fish from the conspecific and mirror trials, showing that overall the behavioral and endocrine response to mirror images and conspecifics was similar. The results show that fight resolution is not necessary to induce an evident increase in peripheral levels of androgens and corticosteroids in B. splendens. However, the function of these hormones during present and future aggressive contests remains to be clarified.
Keywords: Aggression; Androgens; Corticosteroids; Live conspecific test; Mirror test

Triggering a Change of The Economic Paradigm - Rothlin, Stephan (The Journal of the Macau Ricci Institute, 2021)

Un nuovo paradigma economico.(“Ideas for a New Economic Paradigm”) - Rothlin, Stephan (La Civiltà Cattolica, 2021)
La crisi del Covid-19 ha evidenziato il disagio e il divario sempre più ampio tra ricchi e poveri. La crisi finanziaria del 2007-2009 era già risuonata come un campanello d'allarme sulla necessità di

Towards an efficient prognostic model for fetal state assessment - Silva Neto, Manuel Gonçalves da; Madeiro, João Paulo do Vale; Marques, João Alexandre Lobo; Gomes, Danielo G. (Measurement, 2021)
Monitoring signals such as fetal heart rate (FHR) are important indicators of fetal well-being. Computer-assisted analysis of FHR patterns has been successfully used as a decision support tool. However, the absence of a gold standard for the building blocks decision-making in the systems design process impairs the development of new solutions. Here we propose a prognostic model based on advanced signal processing techniques and machine learning algorithms for the fetal state assessment within a comprehensive evaluation process. Feature-engineering-based and time-series-based machine learning classifiers were modeled into three data segmentation schemas for CTU-UHB, HUFA, and DB-TRIUM datasets and the generalization performance was assessed by a two-way cross-dataset evaluation. It has been shown that the feature-based algorithms outperformed the time-series ones on data-limited scenarios. The Support Vector Machines (SVM) obtained the best results on the datasets individually: specificity (85.6% ) and sensitivity (67.5%). On the other hand, the most effective generalization results were achieved by the Multi-layer perceptron (MLP) with a specificity of 71.6% and sensitivity of 61.7%. The overall process provided a combination of techniques and methods that increased the final prognostic model performance, achieving relevant results and requiring a smaller amount of data when compared to the state-of-the-art fetal status assessment solutions.
Keywords: Cardiotocography; Classification; Fetal state assessment; Prognostic model; System design

Physiology, endocrinology and chemical communication in aggressive behaviour of fishes - Silva, Melina Coelho da; Canário, Adelino Vicente Mendonça; Hubbard, Peter Colin; Gonçalves, David (Journal of Fish Biology, 2021)
Fishes show remarkably diverse aggressive behaviour. Aggression is expressed to secure resources; adjusting aggression levels according to context is key to avoid negative consequences for fitness and survival. Nonetheless, despite its importance, the physiological basis of aggression in fishes is still poorly understood. Several reports suggest hormonal modulation of aggression, particularly by androgens, but contradictory studies have been published. Studies exploring the role of chemical communication in aggressive behaviour are also scant, and the pheromones involved remain to be unequivocally characterized. This is surprising as chemical communication is the most ancient form of information exchange and plays a variety of other roles in fishes. Furthermore, the study of chemical communication and aggression is relevant at the evolutionary, ecological and economic levels. A few pioneering studies support the hypothesis that aggressive behaviour, at least in some teleosts, is modulated by “dominance pheromones” that reflect the social status of the sender, but there is little information on the identity of the compounds involved. This review aims to provide a global view of aggressive behaviour in fishes and its underlying physiological mechanisms including the involvement of chemical communication, and discusses the potential use of dominance pheromones to improve fish welfare. Methodological considerations and future research directions are also outlined.

Modelling the barriers that are preventing e-commerce to thrive – a case study from Portugal, international journal of business excellence - Silva, Susana Costa e; Machado, Joana Costa; Martins, Carla; Duarte, Paulo; Marques, João Alexandre Lobo (International Journal of Business Excellence, 2021)
The identification of barriers for e-commerce to thrive in specific countries is a topic of great interest. This work proposes two models to study the barriers to B2C e-commerce adoption in Portugal, highlighting obstacles less exploited by previous research: the impact of offline shopping pleasure and the influence of the distance to shopping malls on online shopping intent. An online survey was conducted based on different constructs. A multivariate OLS hierarchical regression was used to analyse the proposed models regarding the intention to buy online and the number of online purchases. The results revealed that customer satisfaction is a strong predictor of intent to buy online and that perceived product risk remains a barrier to e-commerce. Consumers living in high urbanised areas have more propensity to buy online. Helpful information is provided regarding the impact of context, culture, product, and individual barriers, showing that multichannel strategies are best suited for success.
Keywords: E-commerce barriers; Online shopping; Portugal; Retail

Transforming struggling reform implementers into effectual reform agents: Hong Kong preschool teachers’ voices on process drama - Tam, Po Chi; Sun, C. R. (Youth Theatre Journal, 2021)

The use Robotics in the intervention with children with ASD in Macao: a pilot study with Milo - Teixeira, Vitor; Lai, Michael (Revista Portuguesa de Investigação Educacional, 2021)
Robotics are being used in the intervention with children with Autism Spectrum Disorder (ASD) in many places and already for many years. Many robots were developed and different studies are being made in order to evaluate its effectiveness. “Socially Assistive Robotics” is shown to be effective in different areas mainly in social and emotional development. Milo, a robot developed by a team led by Richard Margolin for the Robots4Autism program (RoboKind, 2020), is one of the robots whose use is reported to be successful. In Macao there is no report of studies or experiences on the use of robots in the intervention with children with ASD. In a collaboration between the Macao Science Centre, the Macao Autism Association (MAA) and the University of Saint Joseph, an exploratory study was developed to understand the applicability of Milo to the work with children with ASD in Macao. The study showed that the robot is able to facilitate social and emotional competences of children with ASD. However, several limitations including language, cultural differences, the inexperienced facilitators and the level of sessions are too simple for the participants to be aware of that may affect the effectiveness of the intervention. It is important to show that the adoption of Milo in Macao for intervening children with ASD can be further implemented, with better practical solutions.

A network analysis investigation of the comorbidity between sleep dysfunction and PTSD symptomatology among Filipino domestic workers in Macao (SAR) China- ClinicalKey - Wang, Siyuan; Sit, Hao Fong; Garabiles, Melissa R.; Blum, Daniel; Hannam, Kevin; Armour, Chérie; Hall, Brian J. (Journal of Psychiatric Research, 2021)

Origin of the Qiyugou gold deposit in the southern margin of the North China Craton: Insights from trace elements of pyrite and mineralogy of Bi-minerals - Wu, Qiang; Zhao, Tai-Ping; Chen, Wei Terry; Gao, Xin-Yu; Meng, Lei; Qiu, Wenhong Johnson (Ore Geology Reviews, 2021)
The Qiyugou gold deposit, located in the Xiong’ ershan area of the North China Craton, contains abundant bismuth-sulfosalts that are closely associated with gold mineralization. Pyrite is the dominant Au-hosted mineral, and has been formed in three generations (Py1, Py2, and Py3). Py1 grains, generally intergrown with milky quartz, are coarse (>1 mm), euhedral in shape, and Au-depleted in composition. In contrast, subhedral Py2 grains, associated with light gray quartz, are medium to coarse (0.2–3 mm) and are enriched in gold that is both invisible and visible. Py3 grains (0.1–0.5 mm), intergrown with abundant sulfide minerals, are relatively fine and Au-depleted. The time-resolved LA-ICP-MS depth profiles of the Py2 grains indicate that invisible gold occurs as either solid solution or nano-particles of native gold and electrum. Visible gold occurs as small blebs in the Py2 grains where inclusions of native bismuth, galenobismutite, lillianite homologs, tetradymite, and galena are also present. In addition, it is common that electrum in microfracture infillings or along grain boundaries of the Py1 and Py2, are intergrown with bismuthinite derivatives, Bi-Cu sulfosalts, emplectite, tetradymite, chalcopyrite, galena, and Py3. Based on textural relationships and mineral assemblages, calculation of physicochemical conditions show that gold was formed in conditions of fTe2 = ~10−11 and fS2 = ~10−11 to 10−12 for Py2, and fTe2 = ~10−9 to 10-11and fS2 = ~10−10 to 10−11 for Py3. We thus proposed that such physicochemical conditions may have triggered the precipitation of Bi melt, and sulfidation driven by cooling or increase in sulfur content results in the transformation of the Au-Bi liquid into a stable assemblage of native gold and bismuthinite. These bismuth minerals are associated with native gold/Au-bearing minerals, indicating that the Au mineralization of the Qiyugou gold deposit might be genetically associated with Bi melt. The present study highlights the role of Bi as important gold scavengers in arsenic-deficient ore-forming fluid.
Keywords: Bi melts scavenging Au; Bismuth minerals; Qiyugou gold deposit; The southern margin of the North China craton; Trace element of pyrite

Learning dynamics of kernel-based deep neural networks in manifolds - Wu, Wei; Jing, Xiaoyuan; Du, Wencai; Chen, Guoliang (Science China Information Sciences, 2021)

Power Allocation for 5G Mobile Multiuser Cooperative Networks - Yin, Fagen; Du, Wencai (Journal of Advanced Transportation, 2021)
With the fifth generation (5G) communication technology, the mobile multiuser networks have developed rapidly. In this paper, the performance analysis of mobile multiuser networks which utilize decode-and-forward (DF) relaying is considered. We derive novel outage probability (OP) expressions. To improve the OP performance, we study the power allocation optimization problem. To solve the optimization problem, we propose an intelligent power allocation optimization algorithm based on grey wolf optimization (GWO). We compare the proposed GWO approach with three existing algorithms. The experimental results reveal that the proposed GWO algorithm can achieve a smaller OP, thus improving system efficiency. Also, compared with other channel models, the OP values of the 2-Rayleigh model are increased by 81.2% and 66.6%, respectively.

Resource estimation of the sulfide-rich deposits of the Yuhuang-1 hydrothermal field on the ultraslow-spreading Southwest Indian Ridge - Yu, Junyu; Tao, Chunhui; Liao, Shili; Dias, Ágata; Liang, Jin; Yang, Weifang; Zhu, Chuanwei (Ore Geology Reviews, 2021)
Seafloor massive sulfide (SMS) deposits are important deep-sea mineral resources expected to occur predominantly on slow- and ultraslow-spreading mid-ocean ridges. Resource estimates are already available for some of the largest SMS deposits on slow-spreading ridges but not on ultraslow-spreading ridges. Based on geological mapping and sampling, this study investigates the distribution and content of sulfide-rich deposits in the Yuhuang-1 hydrothermal field (YHF), located on the ultraslow-spreading Southwest Indian Ridge. The sulfide-rich deposits in the YHF are composed of two areas ∼500 m apart: the southwest sulfide area (SWS) and the northeast sulfide area (NES). We calculated the volume of sulfide-rich mounds in the YHF and arrived at a total accumulation of ∼10.6 × 106 tons, including at least ∼7.5 × 105 tons of copper and zinc and ∼18 tons of gold. Furthermore, considering the coverage of layered hydrothermal sediment mixed with sulfide-rich breccias, which may have underlying massive sulfide deposits, the maximum total mass was estimated at ∼45.1 × 106 tons. This suggests that the YHF is one of the largest SMS deposits worldwide and confirm that ultraslow-spreading ridges have the greatest potential to form large-scale SMS deposits.
Keywords: Resource estimate; Seafloor massive sulfide deposits; Southwest Indian Ridge; Yuhuang-1 hydrothermal field

Occurrence and remobilization of gold in the Dayingezhuang deposit in Jiaodong, North China Craton: Evidence from textural and geochemical features of pyrite - Yuan, Zhong-Zheng; Li, Zhan-Ke; Li, Jian-Wei; Zhao, Xin-Fu; Wu, Ya-Fei; Xu, Hai-Jun; Sun, Hua-Shan (Ore Geology Reviews, 2021)
The Dayingezhuang gold deposit in the Jiaodong district, eastern margin of the North China Craton is hosted in Mesozoic granitic rocks and consists of quartz-sulfide veins/veinlets and sulfide disseminations in alteration envelopes. Previous studies mainly focused on the geochronology, sources of ore-forming fluids and metals to investigate the ore genesis. However, enrichment mechanism of Au and other associated trace metals remain unclear. In this study, we present detailed textures and in-situ LA-ICP-MS trace-element compositions of different generations of pyrite, as well as EMP analysis of Au-bearing minerals to discuss the occurrence and enrichment mechanism of Au at this deposit. Three generations of pyrite (Py1, Py2 and Py3) formed during three hydrothermal ore stages (I, II, and III) at Dayingezhuang. Py1 occurs as disseminations in sericitic alteration assemblages and is characterized by low Au (mean 0.15 ppm), Ag, As and Te contents. The time-resolved depth-concentration profiles indicate that Au in Py1 mainly occurs as nanoparticles and/or micron-sized inclusions. Py2 can be further divided into the early undeformed Py2a and later Py2b, which is the product of deformed Py2a with different degrees of brittle to plastic deformation and recrystallization. Py2a in pyrite-siderite-quartz veins is relatively enriched in invisible Au (mean 0.41 ppm), Ag, As, and Te compared to Py1, and contains numerous micron-sized Au inclusions. In contrast, Py2b contains lesser invisible Au (0.21 ppm) and host abundant gold minerals along the grain boundaries and microfractures. Py3 in polymetallic sulfide veins has little Au. As a whole, Au in pyrite is positively correlated with Ag and Te, which is consistent with the results of EMP analysis showing the occurrence of Au as electrum, native gold and minor petzite in pyrite. Such evidences show that the deformation and recrystallization of auriferous Py2a potentially caused local remobilization of Au (mainly as micron-sized inclusion Au) via solid-state ductile flow and subsequent reconcentration of Au in microfractures of Py2b. The pyrite deformation and Au remobilization events were suggested to be related to the continuous reactivation of the regional Zhaoping Fault contemporaneous with gold mineralization. Our study highlights the importance of remobilization and reconcentration of Au triggered by syn-ore tectonic activities at Dayingezhuang and possibly other Au deposits in the Jiaodong district.
Keywords: Dayingezhuang; EBSD; Gold remobilization; Jiaodong; Pyrite deformation